A systematic literature review on e-commerce logistics: towards an e-commerce and omni-channel decision framework. Issue 1 (1st January 2023) - Risberg, Andreas
ABSTRACT: e-Commerce is the fastest-growing sales channel, while omni-channel retailing is becoming the new retailing standard. Omni-channel logistics is an essential complex aspect of omni-channel retailing, especially considering the increased consumer demand for seamless shopping experiences. This systematic literature review aims to synthesize the contemporary e-commerce logistics literature and to develop a logistics decision framework. This review shows how the focus of e-commerce logistics literature has evolved to multi-channel logistics, and lately to omni-channel logistics. The recent boom in omni-channel logistics publications highlights the importance of logistics in omni-channel retailing with increased complexity and a myriad of logistics design options. An omni-channel logistics decision framework covering 43 decision elements within supply and internal distribution, last mile consumer steering, last mile back-end fulfilment, last mile delivery, and reverse logistics is created by synthesizing 373 articles. This review identifies research opportunities and encourages researchers to complement existing narrower studies with broader empirical studies focusing on the elements' interplay, and configuration studies associated with firm performance. The framework and future research avenues support retail executives in designing logistics, in decision-making and in developing strategies.